Suboptimal nonlinear predictive controllers - Declercq, Filip; Keyser, Robin de (Zielona Góra: Uniwersytet Zielonogórski)
Predictive control based on linear models has become a mature technology in the last decade. Many successful real-time applications can be found in almost every sector of industry. Nonlinear predictive control can further increase the performance of this easy-to-understand control strategy.
Keywords: predictive control; nonlinear control; sequential quadratic programming; diophantine equations